Guillain-Barré syndrome in patients with multiple myeloma: three cases report and literature review - Zhichao Li; Fang Huang; Siguo Hao (BMC Neurology)
Abstract Background Multiple myeloma (MM) with Guillain-Barré syndrome (GBS) is relatively rare, and the specific mechanism is still unclear. The previous infection, surgery, and medication use may have contributed to the occurrence of GBS. The use of bortezomib in patients with MM can easily lead to peripheral neuropathy, which is similar to the symptoms of GBS, making it challenging to diagnose GBS. Cases presentation Three patients with IgA type MM experienced lower limb weakness during treatment. Combined with lumbar puncture, nerve conduction studies, and other tests, the diagnosis was confirmed as GBS. All three patients had a history of spinal surgery before the onset of GBS, and had been treated with bortezomib which induced peripheral neuropathy. Two of the three patients had a clear history of upper respiratory tract infection before the onset of GBS. After treatment with intravenous immunoglobulin, one patient died and two patients showed improvement in GBS symptoms. Conclusion Patients with MM often have concurrent infections and spinal surgery, which may contribute to the occurrence of GBS. The symptoms of bortezomib-induce peripheral neuropathy overlap with those of GBS, which can easily lead to misdiagnosis or missed diagnosis of GBS. Timely lumbar puncture and nerve conduction studies may help to diagnose GBS and improve the prognosis.